2018
DOI: 10.1111/1475-6773.12841
|View full text |Cite
|
Sign up to set email alerts
|

Impact of In‐Hospital Death on Spending for Bereaved Spouses

Abstract: Bereaved spouses of decedents who died in the hospital had significantly greater Medicare spending and health care utilization themselves after their spouses' death.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 61 publications
(95 reference statements)
0
7
0
Order By: Relevance
“…Families report worsened physical and mental health and more hospitalizations following a loved one's death when intensive, life-sustaining treatments were performed at the end of life. [11][12][13] On the other hand, comfortfocused treatments including hospice are associated with decreased depression. 11,14,15 Additionally, bereavement itself is associated with negative consequences for spouses, including not only increased mortality 16 but also reduced personal health maintenance and increased health care expenditures.…”
mentioning
confidence: 99%
“…Families report worsened physical and mental health and more hospitalizations following a loved one's death when intensive, life-sustaining treatments were performed at the end of life. [11][12][13] On the other hand, comfortfocused treatments including hospice are associated with decreased depression. 11,14,15 Additionally, bereavement itself is associated with negative consequences for spouses, including not only increased mortality 16 but also reduced personal health maintenance and increased health care expenditures.…”
mentioning
confidence: 99%
“…The primary outcome was patient-reported occurrence of a goals-of-care conversation during a target outpatient visit. Secondary outcomes included clinician documentation of a goals-of-care conversation in the medical record, patientreported quality of communication measured by the Quality of Communication questionnaire 6 at two weeks, patient Integrating a collaborative care approach to improve depression and fatigue for patients with heart failure Bekelman et al 18 Assessing spousal needs from diagnosis of their partner's illness through bereavement Ornstein et al 25…”
Section: Summary and Main Findings: Priming Interventions In Goals-of-care Conversationsmentioning
confidence: 99%
“…Research has shown that low intensity end-of-life care, such as hospice and palliative care services provided in the home setting, mitigates the negative effect of caregiving by decreasing depression, and increasing quality of death and adjustment to death of the loved one. 25 In the article, Impact of In-Hospital death on Spending for Bereaved Spouses, the authors sought to examine how patients' location of death relates to health care utilization and spending for surviving spouses. The study was an observational study.…”
Section: A Focus On Caregiversmentioning
confidence: 99%
“…13 More intensive treatment is often associated with worse caregiver bereavement. 14,15 A fundamental knowledge gap is that studies evaluating prognostic accuracy have focused predominantly on survival predictions, but prognostication can involve predictions about both quantity and quality of life, 16,17 and quality of life outcomes are fundamental to patients' decision-making when seriously ill. 18 The extent to which oncologists, patients with advanced cancer, and caregivers can accurately predict patients' future quality of life is unclear. To our knowledge, there has been no research on whether these predictions are associated with end-of-life care and caregiver bereavement.…”
Section: Introductionmentioning
confidence: 99%
“…Caregivers routinely participate in treatment decisions, 9–11 and they may also overestimate patient survival, 4,12 with implications for more intensive end‐of‐life treatments 13 . More intensive treatment is often associated with worse caregiver bereavement 14,15 . A fundamental knowledge gap is that studies evaluating prognostic accuracy have focused predominantly on survival predictions, but prognostication can involve predictions about both quantity and quality of life, 16,17 and quality of life outcomes are fundamental to patients' decision‐making when seriously ill 18 .…”
Section: Introductionmentioning
confidence: 99%